Toorlelies (Portfeulje) & Mythopoeia in Marina Tsvetaeva's after Russia (Essay) - Louw, Juanita (Department of English Language and Literature, 2014)
Abtract of essay: Mythopoeia in Marina Tsvetaeva's after Russia. This study examines the use of myth in Marina Tsvetaeva's last poetry collection, After Russia. The study will focus on the myth of Orpheus, the archetypal poet, as well as the metamorphoses of the Greek bard as presented by Tsvetaeva in her poetry. Tsvetaeva's appropriation of the mythic personae of Eurydice and the Cumaean Sibyl will also be explored in relation to the Orphic myth and the way these characters were used to express the comingVintoVbeing of the poet. A brief overview will be given of the mythical figures under discussion as they appear in literature. The study will then consider Tsvetaeva's use of these mythic characters to elucidate her poetic philosophy, the task of the poet and the essence of poetry. Finally, for background information, a short biographical sketch is included.